Impact of Quality, Perceived Value, and Expectations on Satisfaction of Blood Donors of Rasht Blood Transfusion Organization - Vatani, Javad (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Attracting donors and increase their satisfaction for regular donation of blood transfusion are the most important goals of the organization (the blood transfusion organization of Iran). In this study, quality, perceived value, and expectations on the satisfaction level of blood donors in Rasht blood donors were studied. Methods: In this study, the purpose and terms are descriptive survey research. The research instrument was a standard questionnaire. The population of this study included 384, the number of samples and sampling of blood donor transfusion in the center of Rasht were available. Data analysis using software SPSS18 and PLS indicators and descriptive and inferential statistics were used. Results: The results showed that service quality has an impact on the value perceived by donors. Service quality has an impact on increasing donor satisfaction. Perceived value affects blood donors to increase their satisfaction. Conclusion: With attention to customers, the service quality and perceived value affect the level of donor satisfaction, we expected that employees have more responsibility and are ready to service the customers and so the time of doing the customer application should be shorter and appearance of regular employees should be justified. Amenities such as chairs and reception furniture should be appropriate. The referring to customer complaints should be addressed. Staff should have the necessary capabilities that customers feel good about the organization.